HYBRID GENETIC ALGORITHM TO THE SYNTHESIS OF OPTIMAL HEAT EXCHANGER NETWORKS - Ravagnani, M. A. S. S.; Silva, A . P.; Constantino, A. A. (Revista de Engenharia Térmica, 2005)
In this paper a new systematic is proposed, interfacing Pinch Analysis and Genetic Algorithms (GA). Initially the optimal ∆Tmin is found by using a genetic algorithm. In a second step, with the optimal ∆Tmin, the pinch point is obtained, and the problem is divided in two regions, below and above it. The optimal HEN is obtained for each side of the pinch and the final HEN is achieved. An example from the literature was solved using the proposed systematic. Results show the applicability of the proposed methodology, obtaining a cost value lower than those presented in the literature.